A trajetória da Democracia Socialista : da fundação ao PT - Angelo, Vitor Amorim de (Universidade Federal de São Carlos, 2007)
The dissertation analyzes the Socialist Democracy s (DS) trajectory between 1979, year of its foundation, and 1987, when the resolution about the Brazilian Workers Party s (PT) internal trends was approved. The DS was created on the strength of the unification of regional groups that acted in the student movement along with old left militants and since its beginning it contributed to the creation of the PT. During this period, the Socialist Democracy was one of the organizations that grew the most inside the party, holding managerial positions in its board, enjoying good relationships with its management and having most of its proposals incorporated by the PT. The hypothesis of this work is that this growth was a result of the performance marked by critiscism of the party and its leadership, and also because of the support to its management and respect of their own decisions, in an intermediate position that differentiated the Socialist Democracy of other PT s left organizations, especially that of the trotskists.
Keywords: Organização política; Democracia Socialista; Partido dos trabalhadores; Movimento estudantil; Tendência política; Trotskismo; Socialist democracy; Brazilian worker s party; Student movement; Political trends; Trotskism; CIENCIAS HUMANAS::CIENCIA POLITICA